2019
DOI: 10.1519/jsc.0000000000002400
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition of Women's Ice Hockey Players: Comparison of Estimates Using Skinfolds and iDXA

Abstract: The purpose of this study was to compare percent fat (% Fat) estimates from anthropometric equations using skinfolds (SKF) in women's ice hockey players to estimates obtained from Lunar iDXA. Data were collected on 19 elite female Swedish hockey players (mean age ± SD = 18.4 ± 2.4 y). Four skinfolds (SKF) (triceps, abdominal, suprailiac, and thigh) were measured within two hours of iDXA assessments. The % Fat estimates from iDXA and four anthropometric equations were compared using paired t-tests, and a one-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Female ice hockey athletes in this study were taller (1.64-1.66 m), weighed more (67.3-69.8 kg), and had greater amount of lean muscle mass (45.8-49.4 kg) yet had a similar total percent body fat (25.6-28.6 %) compared to previous studies in female ice hockey athletes [12,16,20,21]. Unlike the males in this study, there were positional differences in female ice hockey athletes with F weighing less than D and G and having lower fat and lean mass than the other two positions.…”
Section: Male Femalementioning
confidence: 44%
“…Female ice hockey athletes in this study were taller (1.64-1.66 m), weighed more (67.3-69.8 kg), and had greater amount of lean muscle mass (45.8-49.4 kg) yet had a similar total percent body fat (25.6-28.6 %) compared to previous studies in female ice hockey athletes [12,16,20,21]. Unlike the males in this study, there were positional differences in female ice hockey athletes with F weighing less than D and G and having lower fat and lean mass than the other two positions.…”
Section: Male Femalementioning
confidence: 44%
“…Optimization of body composition promotes optimal performance in ice hockey players [ 4 , 9 , 10 , 11 ]. Additional lean body mass contributes to power generation and speed, and reduced fat mass decreases frictional resistance during skating, so it is of great importance to assess body composition with accuracy and precision [ 12 ]. Indeed, talent identification processes have been developed based on the assessment of anthropometric profiles, which vary according to play position [ 2 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the inherent characteristics of ice hockey and its environmental conditions have nutritional implications for maintaining energy, carbohydrate availability, and fluid balance, which could affect health status and performance [ 12 , 26 ]. Nonetheless, team sport athletes, including ice hockey players, do not usually meet their dietary intake recommendations and report eating disorders such as restrictive eating, low energy intake, or nutrient deficiencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that training programs should be adjusted for individual players to correct these asymmetries (9). The need for proper strength and conditioning programs for athletes to improve physiological gains and symmetries, such as improvement in lean-tissue mass, and optimization of performance while preventing decrements during the season was also emphasized by other authors (6,10,14,35). Thus, investigating different anthropometric parameters such as asymmetries in body composition in ice hockey players may serve as a preventive measure to reduce the risk of injuries and from the vantage point of strengthening the performance of the team (11,35).…”
Section: Introductionmentioning
confidence: 99%